Psychoactive Drug Abuse in Hong Kong Life Satisfaction and Drug Use - Cheung, Yuet Wah (Quality of Life in Asia, 2018)
This book studies young people's use of psychoactive drugs and its social and psychological correlates in Hong Kong. Specifically, it focuses on how life satisfaction may affect drug use among a sample of psychoactive drug users in Hong Kong. The book addresses the dearth of research on the role of young people's life satisfaction in their drug abuse and engagement in other risk behaviors in Hong Kong. It also examines how changes in the drug scene from heroin addiction to psychoactive party drug use since the late 1990s has necessitated a deeper exploration of the subculture of young people, which shapes their attitudes and behaviors regarding how they structure their lives and how they perceive the risks of drug use, in the context of the global trend of normalization of recreational drug use. Readers will benefit from the results of a rigorous analysis of a unique set of longitudinal data that reveals the factors influencing drug use among young psychoactive drug users, academic implications of the findings for social science theory and research on young people's drug use, and practical implications of the findings for prevention and intervention services for young people in Hong Kong and other Asian societies.